2019
DOI: 10.1016/j.jmb.2019.01.041
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Mechanisms Underlying Hidden Phenotypic Variation among Metallo-β-Lactamases

Abstract: Genetic variation among orthologous genes has been largely formed through neutral genetic drift to maintain the same functional role. In some circumstances, however, this genetic variation can create critical phenotypic variation, particularly when genes are transferred to a new host by horizontal gene transfer (HGT). Unveiling "hidden phenotypic variation" through HGT is especially important for genes that confer resistance to antibiotics, which continue to disseminate to new organisms through HGT.Despite thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 81 publications
1
21
0
Order By: Relevance
“…We uncover a lack of optimization in the signal peptide of VIM-2, that may be due to codon dependent RNA folding or incompatibility with the host translocation system. Such findings highlight the importance of genome and host context in resistance gene compatibility 23,60,65 . By performing DMS at various conditions, three different antibiotics, and two temperatures, we enhance the understanding of sequence-structure-function relationships by unveiling a set of mutations for protein stability, catalysis and substrate specificity of VIM-2.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…We uncover a lack of optimization in the signal peptide of VIM-2, that may be due to codon dependent RNA folding or incompatibility with the host translocation system. Such findings highlight the importance of genome and host context in resistance gene compatibility 23,60,65 . By performing DMS at various conditions, three different antibiotics, and two temperatures, we enhance the understanding of sequence-structure-function relationships by unveiling a set of mutations for protein stability, catalysis and substrate specificity of VIM-2.…”
Section: Resultsmentioning
confidence: 81%
“…The less than optimal residue level fitness of wtVIM-2 may be because we employ E. coli as a host while natural VIM variants are often found in Pseudomonas 62 , and/or the signal peptide is not selected to produce maximum expression in natural environments. It has been shown that different signal peptides produce variable expression levels and translocation rates for a given protein, both of which affect the final resistance, especially in different host organisms 23,57,58,[63][64][65] . Furthermore, the signal peptide is frequently mutated in naturally occurring VIM-type variants (see section on 'Natural VIM variation' below), suggesting changes in the signal peptide sequences may have played significant roles in dissemination of MBL genes to different hosts and adaptation to higher antibiotic concentrations.…”
Section: Codon and Amino Acid Optimization In The Signal Peptidementioning
confidence: 99%
See 1 more Smart Citation
“… 39 In addition, the expression of the same class B and D β-lactamases in different hosts exhibited a lack of correlation between MICs and the catalytic efficiency of these enzymes. 43 , 44 Hence, phenotypic variation can be due to differences in catalytic efficiency in the periplasmic conditions, but expression level, protein folding and translocation to the periplasm can also play a role. 43 …”
Section: Discussionmentioning
confidence: 99%
“… 43 , 44 Hence, phenotypic variation can be due to differences in catalytic efficiency in the periplasmic conditions, but expression level, protein folding and translocation to the periplasm can also play a role. 43 …”
Section: Discussionmentioning
confidence: 99%